(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the relationship between effective political reforms and the enhancement of a state’s image, using the cases of the Republic of Korea and the Republic of Uzbekistan. It argues that in contemporary international relations, the image of a state is shaped not only by economic growth, military power, or cultural attractiveness, but also by the quality of political institutions, the degree of transparency in public administration, the effectiveness of anti-corruption policy, the digitalization of public services, the protection of human rights, and the government’s capacity to respond to public demands. The Republic of Korea demonstrates the experience of transition from an authoritarian model to a democratic, technologically advanced, and internationally recognized state. Uzbekistan, in turn, has been implementing a large-scale program of political, legal, and administrative reforms since 2016, aimed at forming the image of an open, modernizing, and responsible state. The article provides a comparative analysis of the two cases, identifies common patterns and distinctive features, and formulates conclusions regarding the significance of consistency, institutional sustainability, and public legitimacy of reforms for strengthening the international image of the state.